1986
DOI: 10.1002/ajmg.1320250103
|View full text |Cite
|
Sign up to set email alerts
|

Animal model: The mode of inheritance of craniomandibular osteopathy in west highland white terrier dogs

Abstract: Craniomandibular osteopathy is a disease of several breeds of dogs, principally West Highland White and Scottish terriers. It is characterized by a non-neoplastic proliferation of bone on the ramus of the mandible and/or the tympanic bulla. The disease in various respects resembles Paget's disease and infantile cortical hyperostosis of humans. A retrospective pedigree analysis of a kindred of West Highland White terriers was performed to determine if the trait was inherited and to determine mode of inheritance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
12

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 4 publications
0
31
0
12
Order By: Relevance
“…1975, 1995; Taylor et al . 1995) and has been found to be an inherited disorder in West Highland white terriers, although it can occur in other breeds especially terrier breeds (Padgett and Mostosky 1986; LaFond et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1975, 1995; Taylor et al . 1995) and has been found to be an inherited disorder in West Highland white terriers, although it can occur in other breeds especially terrier breeds (Padgett and Mostosky 1986; LaFond et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…note that, although not currently reported in horses, craniomandibular osteopathy is a disease similar to HO in that it involves proliferation of long bones. This disease occurs in young dogs resulting in bilateral osseous proliferation of the mandible, tympanic bullae and less commonly other bones of the head (Watson et al 1975(Watson et al , 1995Taylor et al 1995) and has been found to be an inherited disorder in West Highland white terriers, although it can occur in other breeds especially terrier breeds (Padgett and Mostosky 1986;LaFond et al 2002). It is possible that the mandibular and facial involvement observed in the horses of the current report is indicative not of HO but represents a disease distinctive to HO and potentially closer to what has been reported in dogs (craniomandibular osteopathy).…”
Section: Fig 4: a Lateromedial Radiograph Of The Mid-diaphysis Of Thementioning
confidence: 99%
“…Craniomandibular osteopathy is hereditary in West Highland White Terriers and an inherited form of infantile cortical hyperostosis also exists. 12,14 Genetic studies in humans suggest that the familial form of infantile cortical hyperostosis may be associated with a COL1A1 missense mutation. 12,15 It is possible that calvarial hyperostosis syndrome in bullmastiffs also has a partial genetic basis.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness (11 mm) of the median calvaria was exactly the same as that noted on MRI. Thick coarse-fibered trabeculae and areas of bone substance rarefaction were observed, and metaphyseal osteopathy and craniomandibular osteopathy respectively as conditions resembling Paget's disease [5,10]. Although there are unclear points, from the clinical manifestations and images noted in the case reported herein, if Paget's disease exists in dogs, then it would be intriguing to speculate that dogs may play an important role in human Paget's disease.…”
mentioning
confidence: 82%